mcrA-Targeted Real-Time Quantitative PCR Method To Examine Methanogen Communities - Steinberg, Lisa M. (American Society for Microbiology (ASM), 2009)
Methanogens are of great importance in carbon cycling and alternative energy production, but quantitation with culture-based methods is time-consuming and biased against methanogen groups that are difficult to cultivate in a laboratory. For these reasons, methanogens are typically studied through culture-independent molecular techniques. We developed a SYBR green I quantitative PCR (qPCR) assay to quantify total numbers of methyl coenzyme M reductase α-subunit (mcrA) genes. TaqMan probes were also designed to target nine different phylogenetic groups of methanogens in qPCR assays. Total mcrA and mcrA levels of different methanogen phylogenetic groups were determined from six samples: four samples from anaerobic digesters used to treat either primarily cow or pig manure and two aliquots from an acidic peat sample stored at 4°C or 20°C. Only members of the Methanosaetaceae, Methanosarcina, Methanobacteriaceae, and Methanocorpusculaceae and Fen cluster were detected in the environmental samples. The three samples obtained from cow manure digesters were dominated by members of the genus Methanosarcina, whereas the sample from the pig manure digester contained detectable levels of only members of the Methanobacteriaceae. The acidic peat samples were dominated by both Methanosarcina spp. and members of the Fen cluster. In two of the manure digester samples only one methanogen group was detected, but in both of the acidic peat samples and two of the manure digester samples, multiple methanogen groups were detected. The TaqMan qPCR assays were successfully able to determine the environmental abundance of different phylogenetic groups of methanogens, including several groups with few or no cultivated members.